Makna bentuk simbolik kontrol sosial di Perpustakaan Pusat UIN Maulana Malik Ibrahim Malang - Mufid Mufid (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2018)
The purpose of this study was to understand the meaning of symbolic forms of social control in the Library of UIN Maulana Malik Ibrahim Malang, including rules/orders, ritual activities, spatial and furniture. The study uses an ethnographic approach to describe organizational culture through observation and interviews. This study indicates that symbolic forms, including rules/orders, ritual activities, spatial and furniture, impact staff conduct their duties. This finding contributes knowledge about organizational culture regarding the meaning of symbolic forms of social control in libraries.